2020
DOI: 10.1038/s41598-020-68998-w
|View full text |Cite
|
Sign up to set email alerts
|

PI3K-targeting strategy using alpelisib to enhance the antitumor effect of paclitaxel in human gastric cancer

Abstract: PIK3CA mutations are frequently observed in various human cancers including gastric cancer (GC). This study was conducted to investigate the anti-tumor effects of alpelisib, a PI3K p110α-specific inhibitor, using preclinical models of GC. In addition, the combined effects of alpelisib and paclitaxel on GC were evaluated. Among the SNU1, SNU16, SNU484, SNU601, SNU638, SNU668, AGS, and MKN1 GC cells, three PIK3CA-mutant cells were predominantly sensitive to alpelisib. Alpelisib monotherapy decreased AKT and S6K1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Paradoxical effects of chemotherapy on tumour relapse and metastasis promotion were recognised in recent years 31 . PTX, a drug that induces mitotic arrest due to activation of the mitotic checkpoint, can promote tumour metastasis 13 , 32 . Specifically, PTX-induced tumour metastasis is a complex process involving several molecular mechanisms 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxical effects of chemotherapy on tumour relapse and metastasis promotion were recognised in recent years 31 . PTX, a drug that induces mitotic arrest due to activation of the mitotic checkpoint, can promote tumour metastasis 13 , 32 . Specifically, PTX-induced tumour metastasis is a complex process involving several molecular mechanisms 31 .…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT and Wnt/β-catenin pathways also play a role in synergistic lethality in cancer therapy. In gastric cancer, synergistic lethality for combination therapy with paclitaxel and PI3K p110α-specific inhibitor alpelisib was found to be stronger in PIK3CA-mutant cells related to enhanced DDR and apoptosis, as demonstrated by γ-H2ax and caspase 3/7 assays, respectively ( 149 ). Indeed, Juvekar et al have demonstrated that PI3K3CA inhibition of breast cancer cells by alpelisib can produce raised nucleotide depletion-mediated DNA damage and thus death of cancer cells ( 150 ).…”
Section: Clear Cell Carcinoma Of the Ovarymentioning
confidence: 99%
“…The combination of alpelisib with paclitaxel is currently being studied in breast cancer patients and advanced solid tumors [39,40]. In gastric cancer, alpelisib and paclitaxel demonstrated synergistic anti-proliferative and anti-migratory effects in PIK3CA mutant cells [41]. In a xenograft model utilizing gastric cancer cells, alpelisib and paclitaxel significantly increased apoptosis and tended to prolong the survival of tumor-bearing mice.…”
Section: Pi3k Inhibition In Combination With Chemotherapymentioning
confidence: 99%